(untitled) (CIPEEX, 2024)
UITRAVITAL APPEARS AS SOFTWARE THAT AIMS TO SPEED UP THIS PROCESS BY PROVIDING: PATIENT COMFORT AND SAFETY. ULTRAVITAL’S MAIN GOAL IS TO SIMPLIFY. SCHEDULE DOCTOR APPOINTMENTS BY PROVIDING PATIENTS WITH AN EASY WAY TO SCHEDULE APPOINTMENTS. HOSPITAL VISIT.